2004
DOI: 10.1007/s00213-003-1641-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta-adrenoceptor blockade on components of human decision-making

Abstract: These results suggest that NA modulates the processing of punishment signals when choosing between probabilistic rewards and punishments under conditions of increased arousal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 33 publications
3
66
1
Order By: Relevance
“…These studies have consistently demonstrated changes in participants' attentional processing of potential gains and losses (Rogers et al, 2003(Rogers et al, , 2004Scarna et al, 2005) rather than reducing participants' discrimination between gambles with varying expected value and gambles with zero expected value as seen in the present experiment. This result is reminiscent of the finding that THC sustains participants' choice of response options associated with ever-diminishing reward (Lane and Cherek, 2002) and suggests that cannabinoid activation may play a complementary role to that of the major monoamine systems by mediating sensitivity to altered reinforcement contingencies associated with response options.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…These studies have consistently demonstrated changes in participants' attentional processing of potential gains and losses (Rogers et al, 2003(Rogers et al, , 2004Scarna et al, 2005) rather than reducing participants' discrimination between gambles with varying expected value and gambles with zero expected value as seen in the present experiment. This result is reminiscent of the finding that THC sustains participants' choice of response options associated with ever-diminishing reward (Lane and Cherek, 2002) and suggests that cannabinoid activation may play a complementary role to that of the major monoamine systems by mediating sensitivity to altered reinforcement contingencies associated with response options.…”
Section: Discussionsupporting
confidence: 70%
“…This includes demonstrations that manipulation of serotonergic (Rogers et al, 1999a(Rogers et al, , 2003, catecholamine (Rogers et al, 2004;Scarna et al, 2005) and GABAergic activity (Deakin et al, 2004;Lane et al, 2005a) can influence laboratory models of decision-making. However, at the current time, little is known about the importance of cannabinoid activity in decision-making despite the preponderance of CB 1 receptors within corticolimbic circuitry (Herkenham et al, 1990) and their interactions with other neuromodulatory systems (Ameri, 1999;Tanda et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulation of the serotonin, noradrenaline, and dopamine has been found to alter the processing of reinforcement cues, while healthy participants perform the risky choice used in the current study (Rogers et al, 2003(Rogers et al, , 2004aScarna et al, 2005). Of particular relevance is the finding that dietary depletion of Ltryptophan was associated with reduced attention to possible gains but not losses (Rogers et al, 2003), suggesting that serotonin mediates appetitive aspects of risky choice.…”
Section: Discussionmentioning
confidence: 71%
“…In the present study, we investigated the decision-making of ecstasy users, ecstasy-naïve polydrug users, and drugnaïve controls using a recently devised paradigm, which measures decision-makers' attention to reinforcement signals involved in risky choice: the magnitude of prospective gains (or reward), the magnitude of prospective losses (or punishment), and the probabilities with which each of these outcomes will be delivered (Rogers et al, 2003(Rogers et al, , 2004aScarna et al, 2005). Previously, tryptophandepleted participants showed reduced discrimination between magnitudes of prospective gains associated with different choices in this task (Rogers et al, 2003).…”
Section: Introductionmentioning
confidence: 99%